Daya Simpan Daging Has Luar (Sirloin) Sapi Lokal yang Digiling Pada Suhu Kamar - Harmaini, M.J. Djas (Jurnal Agripet, 2001)
ABSTRACT. This study was carried out to determine reservation time of crushing sirloin meat of local bull in room temperature. Smples used were sirloin meat from six male local bulls, aged 3-4 years old, all of which were slaughtered at slaughter house of Banda Aceh municipality. They were designed into two treatments, 3 cm3Cutting and crushing sirloin meats. Meat docay time was determined by using postma test every 3 hours after the treatment. The results showed that: 1) two samples of 3 cm cutting sirloin meats were dubius at 9 hours, and one sample was dubius at 12 hours, 2) four samples of crushing sirloin meats showed dubius at 6 hours, 3) mean decay 3 time cm3cutting sirloin meats was 11 1.55 hours and that of crushing sirloin meats was 6.5 1.22 hours, 4) the test showed that decay time of 3cm3cutting sirloin meats was significantly longer than that of crushing sirloin meats (P0.01). In conclusion, reservation time of crushing sirloin meats in shorter than that of in crushing sirloin meats.Key Word :Sirloin Meat; Posma Test